HUBUNGAN TINGKAT STRES DAN EATING DISORDER DENGAN STATUS GIZI - Yuri Aini Qalbya; Yohannes Willihelm Saleky; Nitta Isdiany; Gurid PE Mulyo (Jurusan Gizi Poltekkes Kemenkes Bandung, 2022)
Majority of teenagers are stressed out due to the condition of social environment, which eventually triggers the occurrence of abnormal eating behaviors known as eating disorder. This behavior affects the nutritional status of adolescents. Studies in 2020 and 2014 found that there were 67.8% female adolescents with eating disorder and 49,5% with moderate to severe stress. Data from RISKESDAS 2018 show that there was 8.2% underweight adolescents. This study aims to identify the relationship of stress level and eating disorder with nutritional status of the students. This is a Cross Sectional study with the of 67 people taken with the Simple Random Sampling technique. Instruments used were Depression Anxiety Stress Scale questionnaire to determine stress levels, the Eating Disorder Diagnosis Scale questionnaire to determine the level of Eating Disorder and anthropometric measurements to determine nutritional status. Data were analyzed by using Chi-square Test with SPSS program. The results shows that there was 23.8% repondents with underweight. Most of the respondentst (67.2%) were normal and only 9% was overweight. This study also found that 26.9% of respondents were stressed and 73.1% of respondents did not experience stress. There were also 19.4% respondents with bulimia nervosa, 10.4% respondents with EDNOS and 1.5% respondents with Binge Eating Disorder. No significant relationship was found between stress and eating disorder, as well as between eating disorder and nutritional status (p-value: 0.420 and 0.196). It is important for the adolescents to control their stress and diet in order to control their nutritional status.